The role of functional magnetic resonance imaging in clinically diagnosed cases of migraine - Tushar Kalekar; Khushboo Agrawal; Arunima Gupta; Vijetha Chanabasanavar (Asian Journal of Medical Sciences, 2023)
Background: Migraine manifests as recurrent headaches associated with nausea, vomiting, and sensory hypersensitivity. Functional magnetic resonance imaging (fMRI) images activation in different parts of brain either on stimulation or at rest. Aims and Objectives: The aim of the study was to study the fMRI changes in brain in response to visual stimulation in migraine patients with and without aura compared with healthy volunteers. Materials and Methods: A prospective fMRI study was performed in 50 clinically diagnosed cases of migraine and 50 healthy volunteers above 18 years of age on a 3-Tesla MRI scanner. For fMRI, the visual stimulus was presented as a moving black and white checker board pattern. Results: All subjects demonstrated activation in bilateral occipital cortex (predominantly in V1 followed by V2 area). Group analysis of the occipital activation pattern in migraine patients versus control revealed that 56% (28/50) showed significantly increased activation in occipital cortex, 20% (10/50) revealed no significant difference in activation patterns, and 24% of total migraine patients (12/50) had equivocal results. Out of the 28 patients with increased activation in occipital cortex, 14 (50%) revealed increased activation in the left V5 cortex, 8 (28.5%) increased activation in the left V3 cortex, 4 (14.2%) increased activation in both left V3 and V5 cortex, and 2 (7.1%) had increased activation in both right V3 and right V5 areas. Conclusion: The current study revealed increased occipital stimulation mainly in the left V3 and V5 areas in clinically diagnosed cases of migraine in comparison to normal healthy subjects. The study also revealed clinically significant association between increased occipital stimulation and duration of migraine and absence of pharmacological aid.